Comparison of Outcome of Lateral K-Wire Fixation Verses Medio-Lateral Crossed K-Wire Fixation for Displaced Extension Type of Supracondylar Humeral Fractures in Children - Gupta, HK; Chaurasia, D (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Supracondylar humeral fractures are the most common elbow fractures seen in children. The purpose of this study was to compare the efficacy of lateral entry pin fixation with that of medial and lateral entry pin fixation for the operative treatment of displaced extension supracondylar fractures of the humerus in children. MATERIAL AND METHODS: Total of 50 cases of displaced supracondylar fracture humerus were enrolled in study, 25 cases in two equal groups, Group A and group B. Group A received treatment by closed reduction with lateral k-wire fixation and Group B received treatment by closed reduction and medio-lateral k-wire fixation. The cases were followed at 4 weeks when slab was removed and physiotherapy started, and at 12 weeks for final outcome. The outcome was measured as per Flynn's criteria. RESULTS: The mean age of patents in group A was 6.40 years and in group B was 6.44 years. At final follow up, in group A, 18 (72%) cases had excellent, 7 (28%) good result, in group B; 20 (80%) had excellent, and 5 (20%) had good result. The p- value (0.08) derived between them was statistically not significant. Three pateints got superficial pin tract infection in group A and two iatrogenic ulnar nerve injury and one pin had pintract infection in group B. There were also no significant differences (p value- 0.697) between groups with respect to the baumann angle. CONCLUSION: Both lateral entry pin fixation and medio- lateral entry pin fixation are effective in the treatment of completely displaced (type-III) extension supracondylar fractures of the humerus in children. Although there remains subtle risk of ulnar nerve injury in medio-lateral pin fixation. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11823 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 20-25